Endocannabinoid system in systemic lupus erythematosus: First evidence for a deranged 2-arachidonoylglycerol metabolism. (June 2018) - Navarini, Luca; Bisogno, Tiziana; Mozetic, Pamela; Piscitelli, Fabiana; Margiotta, Domenico Paolo Emanuele; Basta, Fabio; Afeltra, Antonella; Maccarrone, Mauro
Abstract: The endocannabinoid (eCB) system plays a key role in many physiological and pathological conditions and its dysregulation has been described in several rheumatological and autoimmune diseases. Yet, its possible alteration in systemic lupus erythematosus (SLE) has never been investigated. Here, we aimed filling this gap in plasma and peripheral blood mononuclear cells (PBMCs) of patients with SLE and age- and sex- matched healthy subjects (HS). Liquid chromatography-mass spectrometry quantitation of eCB levels highlighted that plasma levels of 2-arachidonoylglycerol (2-AG) were significantly increased in SLE patients compared to HS (p = 0.0059), and among SLE patients, highest 2-AG levels were associated with a lower disease activity. No differences were found in N- arachidonoylethanolamine (AEA) and its congeners N -palmitoylethanolamine (PEA) and N -oleoylethanolamine (OEA) concentrations between the two groups. Moreover, gene expression analysis of metabolic enzymes and receptor targets of eCBs and investigation of functional activity and protein expression of selected components of eCB system disclosed a deranged 2-AG metabolism in patients with SLE. Indeed, expression and functional activity of 2-AG biosynthetic enzyme DAGL were selectively enhanced in PBMCs of SLE patients compared to HS. In conclusion, our results demonstrate, for the first time, an alteration of eCB system in SLE patients. They represents the first step toward the understanding of the role of eCB system in SLE that likely suggest DAGL and 2-AG as potential biomarkers of SLE in easily accessible blood samples. Our data provides proof-of-concept to the development of cannabis-based medicine as immune-modulating agents.